Species Diversity, Habitat Distribution, and Blood Meal Analysis of Haematophagous Dipterans Collected by CDC-UV Light Traps in the Dominican Republic - Mikel Alexander González; Daniel Bravo-Barriga; María Altagracia Rodríguez-Sosa; Juan Rueda; Eva Frontera; Pedro María Alarcón-Elbal (Pathogens, 2022)
Haematophagous insects cause major economic losses by both direct damage and the transmission of pathogens. However, the biting Diptera species in the Caribbean region have been poorly documented. During 2021, CDC downdraft suction traps with UV light were employed to assess both the species occurrence and blood meal sources across three different habitats in the Dominican Republic. Eighteen species of mosquitoes (n = 274), six species of Culicoides (n = 803), two black fly species (n = 2), and one species of muscid fly (n = 25) were identified at species-level by morphology and/or molecular phylogenetic approaches based on the mitochondrial cytochrome c oxidase subunit 1 (COI). Engorged mosquito (n = 5) and Culicoides (n = 28) females showed host preferences derived exclusively from mammals (cows and pigs), except Culex species containing the blood of chickens. Our study provides new records of the Diptera Dominican catalogue (Culex salinarius for the Greater Antilles, Culicoides jamaicensis for Hispaniola, and Culicoides haitiensis and Culicoides borinqueni for the Dominican Republic), the first available COI DNA sequences of different Diptera in the GenBank, some pictures of diagnostic features of closely related specimens, spatial distribution across the habitats studied, and new insights on their feeding preferences in the Caribbean region.